2022
DOI: 10.3389/fsurg.2022.873691
|View full text |Cite
|
Sign up to set email alerts
|

The Learning Curve of Unilateral Biportal Endoscopic (UBE) Spinal Surgery by CUSUM Analysis

Abstract: ObjectiveTo assess the learning curve of the unilateral biportal endoscopic (UBE) technique for the treatment of single-level lumbar disc herniation by cumulative summation (CUSUM) method analysis.MethodsA retrospective analysis was conducted to assess 97 patients' general condition, operation time, complications, and curative effect of single segmental UBE surgery performed by a spinal surgeon in his early stage of this technique. The learning curve of operation time was studied using a CUSUM method, and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 41 publications
(45 reference statements)
0
20
0
Order By: Relevance
“…He concluded that the surgical field of vision was expanded with different channels, and vascular bleeding was less under irrigation. The decompression process and instruments of UBE are similar to those used for open posterior discectomy, and thus this procedure can be carried out after only a short training period ( 28 ). Therefore, the learning curve of UBE is relatively flat and short.…”
Section: Discussionmentioning
confidence: 99%
“…He concluded that the surgical field of vision was expanded with different channels, and vascular bleeding was less under irrigation. The decompression process and instruments of UBE are similar to those used for open posterior discectomy, and thus this procedure can be carried out after only a short training period ( 28 ). Therefore, the learning curve of UBE is relatively flat and short.…”
Section: Discussionmentioning
confidence: 99%
“…23 Conventional open surgery requires extensive dissection leading to more muscle damage, ischemia, and muscle atrophy, ultimately causing postoperative pain and, in some cases, poor outcomes. [24][25][26] After recent improvements in surgical techniques, the application of minimally invasive surgeries like minimally invasive transforaminal lumbar interbody fusion (MIS-TLIF) are on the rise as they are superior in terms of better surgical outcomes, early recovery, and minimal damage to tissues compared to conventional open surgeries. [7][8][9][10] Recent advancements in optics and endoscopic devices have enabled better visualization of the anatomy and helped surgeons perform safer decompressive spinal surgery with good clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the choice depends on each patient's spinal anatomy and pathology. Another demerit of CIA-UBE is a technical difficulty with a steep learning curve ( 27 ). In the process of laminotomy, the initial operative field is relatively narrow, and sometimes, a steep operative angle is needed.…”
Section: Discussionmentioning
confidence: 99%